Factors influencing the marketability failure of local fruit produce: farmers and retailers perspective / Siti Maziah Ab Rahman, Wan Noor Hana Abd Aziz and Mohd Shukri Omar - Ab Rahman, Siti Maziah; Abd Aziz, Wan Noor Hana; Omar, Mohd Shukri (2011)
This research is conducted with the objectives of identifying the influential factors to the marketability failure of local fruit. In other words, the study wishes to identify the factors considered important to the farmers and retailers that contribute to the failure of their marketing activities. The study also seeks to identify the nature problems and weaknesses of both the farmers and the retailers in their marketing practices of local fruit produce. The last objective is to rank the most important and least important that influential factors in marketing local fruit. The research covers an area within the state of Kelantan with specific focus on the areas where the selected fruit were abundantly found and grown. This quantitative research used regression analysis in order to identify the relationship between distribution channel, promotion, price, competition and marketability failure. The perspective of the farmers' and retailers' were measured. Failure gaps were ultimately identified. The finding on retailers' perspective revealed that the "competition" factor was the major factor contributing to their marketability failure. Contrary to the farmers felt that "pricing" were the leading factor failing them. The problem faced by the retailers and farmers are not the same. It can be seen that the pricing is the most important factor that lead to the marketability failure for the farmers but it is not to the retailers. The retailers are concerned about the competition. Recommendations addressing the perceived marketability failures were highlighted in the study.